Muscle coordination of mediolateral balance in normal walking - Pandy, Marcus G.; Lin, Yi-Chung; Kim, Hyung Joo (Journal of biomechanics, 2010)
The aim of this study was to describe and explain how individual muscles control mediolateral balance during normal walking. Biomechanical modeling and experimental gait data were used to quantify individual muscle contributions to the mediolateral acceleration of the center of mass during the stance phase. We tested the hypothesis that the hip, knee, and ankle extensors, which act primarily in the sagittal plane and contribute significantly to vertical support and forward progression, also accelerate the center of mass in the mediolateral direction. Kinematic, force plate, and muscle EMG data were recorded simultaneously for five healthy subjects who walked at their preferred speeds. The body was modeled as a 10-segment, 23 degree-of-freedom skeleton, actuated by 54 muscles. Joint moments obtained from inverse dynamics were decomposed into muscle forces by solving an optimization problem that minimized the sum of the squares of the muscle activations. Muscles contributed significantly to the mediolateral acceleration of the center of mass throughout stance. Muscles that generated both support and forward progression (vasti, soleus, and gastrocnemius) also accelerated the center of mass laterally, in concert with the hip adductors and the plantarflexor everters. Gravity accelerated the center of mass laterally for most of the stance phase. The hip abductors, anterior and posterior gluteus medius, and, to a much lesser extent, the plantarflexor inverters, actively controlled balance by accelerating the center of mass medially.